2005
DOI: 10.1007/s00018-005-5313-y
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the importance of selenium and selenoproteins in muscle function

Abstract: Abstract. Selenium is an essential trace element. In cattle, selenium deficiency causes dysfunction of various organs, including skeletal and cardiac muscles. In humans as well, lack of selenium is associated with many disorders, but despite accumulation of clinical reports, muscle diseases are not generally considered on the list. The goal of this review is to establish the connection between clinical observations and the most recent advances obtained in selenium biology. Recent results about a possible role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(121 citation statements)
references
References 67 publications
3
114
0
4
Order By: Relevance
“…This finding is consistent with the idea that selenium plays an important role in normal muscle function [27]. A potential biological mechanism by which selenium could contribute to muscle weakness is through maintenance of an optimal concentration of glutathione peroxidase, a key antioxidant selenoenzyme, and/or selenoprotein W. The serum selenium concentrations among women in the present study were lower than that described among older men and women in the Third National Health and Nutrition Examination Survey, [14] but were not as low as serum selenium concentrations that are associated with overt selenium deficiency.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is consistent with the idea that selenium plays an important role in normal muscle function [27]. A potential biological mechanism by which selenium could contribute to muscle weakness is through maintenance of an optimal concentration of glutathione peroxidase, a key antioxidant selenoenzyme, and/or selenoprotein W. The serum selenium concentrations among women in the present study were lower than that described among older men and women in the Third National Health and Nutrition Examination Survey, [14] but were not as low as serum selenium concentrations that are associated with overt selenium deficiency.…”
Section: Discussionsupporting
confidence: 93%
“…The accumulation of mitochondrial and nuclear DNA damage and increase in oxidative stress may contribute to the loss of myocytes and compromise skeletal muscle function [3]. In higher eukaryotes 26 selenoproteins have been identified [27] and in animals alone 25 have been found; although the function of many of these selenoproteins remains unknown [16]. Of the known selenoproteins, there are three known serum selenium containing proteins: extracellular glutathione peroxidase, selenoprotein P and albumin [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore the spectrum of selenoprotein-related disorders includes rigid spine CMD, multiminicore myopathy, desmin-related myopathy with Mallory body-like inclusions and congenital fiber-type disproportion. rederstorff et al 191 confirmed the importance of selenium-containing proteins in muscle formation, maintenance and repair and attested that in patients with selenoprotein-related disorders most of mutations are nonsense mutations and deletions, likely to induce a loss of function.…”
Section: Therapeutic Perspectivesmentioning
confidence: 97%
“…SelN is the only selenoprotein so far directly linked to a disease (230,265), and unlike the other selenoproteins, its characterization started with a known loss-of-function phenotype. Several forms of early-onset myopathies characterized by hypotonia, weakness, axial muscle impairment, spinal rigidity and life-threatening respiratory failure have been linked to the SelN gene (SEPN1) locus (265).…”
Section: F Selenoprotein Nmentioning
confidence: 99%